An immunoglobulin-like receptor, Allergin-1, inhibits immunoglobulin E–mediated immediate hypersensitivity reactions - 田原 聡子; 渋谷 和子; 渋谷 彰; Hitomi Kaori; Tahara-Hanaoka Satoko; Someya Satoru; Fujiki Akira; Tada Hideaki; Sugiyama Tetsuya; Shibayama Shiro; Shibuya Kazuko; Shibuya Akira (Nature immunology, 2010)
Anaphylaxis is a life-threatening immediate hypersensitivity reaction triggered by antigen capture by immunoglobulin E (IgE) bound to the high-affinity IgE receptor (FcεRI) on mast cells. However, the regulatory mechanism of mast cell activation is not completely understood. Here we identify an immunoglobulin-like receptor, Allergin-1, that contains an immunoreceptor tyrosine-based inhibitory motif (ITIM)-like domain, and show it was preferentially expressed on mast cells. Mouse Allergin-1 recruited the tyrosine phosphatases SHP-1 and SHP-2 and the inositol phosphatase SHIP. Coligation of Allergin-1 and FcεRI suppressed IgE-mediated degranulation of bone marrow–derived cultured mast cells. Moreover, mice deficient in Allergin-1 developed enhanced passive systemic and cutaneous anaphylaxis. Thus, Allergin-1 suppresses IgE-mediated, mast cell–dependent anaphylaxis in mice.